Assessment of sperm DNA integrity within the Palaemon longirostris (H. Milne-Edwards, 1837) population of the Seine estuary. (February 2019) - Erraud, Alexandre; Bonnard, Marc; Geffard, Olivier; Chaumot, Arnaud; Duflot, Aurélie; Geffard, Alain; Forget-Leray, Joëlle; Xuereb, Benoit
Abstract: The interpretation of biomarkers in natura should be based on a referential of expected values in uncontaminated conditions. Nevertheless, to build a reference data set of biomarker responses in estuarine areas, which receive chronic pollution loads due to their transition position between continent and sea, is impossible. In this context, the aim of the present work was to propose the use of laboratory recovery period to define a baseline for the measurement of sperm DNA damage by Comet assay in the estuarine prawn Palaemon longirostris. For that, sperm DNA integrity was observed after both a passive ( i.e . 20 days in a clean environment) and an active ( i.e . forced renewal of spermatophores) recovery of wild P. longirostris specimens from the Seine estuary, in laboratory conditions. Then, the levels of sperm DNA damage recorded within the P. longirostris population of the Seine estuary, during six campaigns of sampling from April 2015 to October 2017, have been interpreted according to the defined threshold values. The results showed a persistence in the level of DNA damage after 20-day in clean environment with the passive recovery. This strategy was inconclusive to reach a baseline level but it revealed the lack of DNA repair mechanisms. For the active recovery, a decrease of 54% of the level of DNA damage has been observed after the first renewal of spermatophores and this level stabilized after the second renewal. On the basis of this second strategy, we defined a mean basal value of sperm DNA damage of 54.9 A.U. and a maximum threshold of 69.7 A.U. ( i.e . 95 %CI). The analysis of the results using the reference value highlighted significant abnormal sperm DNA damage within the native population of P. longirostris from the Seine estuary on all stations during the six-sampling campaigns. Graphical abstract: Highlights: Alternative strategy to propose a baseline of sperm DNA integrity in P. longirostris . Persistence of sperm DNA damages during 20 days after the toxic stress cancelation. Relevance of a significant threshold to discriminate abnormal genotoxic pressure.